Diffuser design and experimental research of a large-scale chilled water storage system. Issue 12 (18th June 2021) - Tang, Jiali; OuYang, Zhengrong; Shi, Yuyang
ABSTRACT: Naturally stratified technology is the most economical and effective method in chilled water storage technique and its core is the design of water diffuser. The better the performance of diffuser and the higher the efficiency of chilled water storage is. With the development of science and technology, many large-scale scientific facilities come into being, most of which need to be equipped with large-scale water storage system and run in the extreme operating conditions. If these water storage systems adopt the naturally stratified technology, it is necessary to optimize the design of the diffuser to achieve an ideal storage efficiency, which can not only save energy but also guarantee the operation of the facilities. The water storage system of Steady High Magnetic Field Facilities is one of the representative water storage systems with large flow rate and large temperature difference. By establishing the discrete equation of heat conduction, the results show that the convection doping related to the design of the diffuser is the primary factor affecting the thickness of thermocline. It was also verified by experiments that the large-scale chilled water storage device with well-designed octagonal diffuser and uniform flow orifice can achieve ideal storage efficiency under the operation conditions of large flow rate and large temperature difference.